Strategi Komunikasi Krisis FH UI dalam Merespons Viralitas Isu Pelecehan Seksual di Media Sosial - Intan Puspitasari; Abdul Aziz; Edison Bonar Tua Hutapea (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the crisis communication strategies implemented by the Faculty of Law, Universitas Indonesia (FH UI) in responding to digital sexual harassment issues involving 16 students from the 2023 cohort. This phenomenon represents an anomaly as it occurred within a legal education institution and involved a massive number of perpetrators within digital spaces. The research method employed is descriptive qualitative with a case study approach. Data were gathered through the observation of official statements on social media platforms and press releases from the UI Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS). The analysis was conducted using the Situational Crisis Communication Theory (SCCT). The results indicate that FH UI implemented diminish and bolstering strategies through transparency in internal hearing processes and the deactivation of perpetrators from student organizations. Although the initial response was considered swift, social media virality reflected significant public pressure on the institution's reputation. This study concludes that coordination between tactical units such as Satgas PPKS and deanery management is crucial in mitigating the impact of reputation crises in the digital era. Furthermore, this research contributes to the development of social media-based crisis mitigation protocols for higher education institutions.